Lignans from Schisandra sphenanthera protect against lithocholic acid-induced cholestasis by pregnane X receptor activation in mice. (5th December 2019) - Fan, Shicheng; Liu, Conghui; Jiang, Yiming; Gao, Yue; Chen, Yixin; Fu, Kaili; Yao, Xinpeng; Huang, Min; Bi, Huichang
Abstract: Ethnopharmacological relevance: Cholestasis is a clinical syndrome caused by toxic bile acid retention that will lead to serious liver diseases. Ursodeoxycholic acid (UDCA) and obeticholic acid (OCA) are the only two FDA-approved drugs for its treatment. Thus, there is a clear need to develop new therapeutic approaches for cholestasis. Here, anti-cholestasis effects of the lignans from a traditional Chinese herbal medicine, Schisandra sphenanthera, were investigated as well as the involved mechanisms. Materials and methods: Adult male C57BL/6J mice were randomly divided into 9 groups including the control group, LCA group, LCA with specific lignan treatment of Schisandrin A (SinA), Schisandrin B (SinB), Schisandrin C (SinC), Schisandrol A (SolA), Schisandrol B (SolB), Schisantherin A (StnA) and Schisantherin B (StnB), respectively. Mice were treated with each drug (qd) for 7 days, while the administration of lithocholic acid (LCA) (bid) was launched from the 4th day. Twelve hours after the last LCA injection, mice were sacrificed and samples were collected. Serum biochemical measurement and histological analysis were conducted. Metabolomics analysis of serum, liver, intestine and feces were performed to study the metabolic profile of bile acids. RT-qPCR and Western blot analysis were conducted to determine the hepatic expression of genes and proteins related to bile acid homeostasis. Dual-luciferase reporter gene assay was performed to investigate the transactivation effect of lignans on human pregnane X receptor (hPXR). RT-qPCR analysis was used to detect induction effects of lignans on hPXR-targeted genes in HepG2 cells. Results: Lignans including SinA, SinB, SinC, SolA, SolB, StnA, StnB were found to significantly protect against LCA-induced intrahepatic cholestasis, as evidenced by significant decrease in liver necrosis, serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) activity. More importantly, serum total bile acids (TBA) and total bilirubin (Tbili) were also significantly reduced. Metabolomics analysis revealed these lignans accelerated the metabolism of bile acids and increased the bile acid efflux from liver into the intestine or feces. Gene analysis revealed these lignans induced the hepatic expressions of PXR-target genes such as Cyp3a11 and Ugt1a1 . Luciferase reporter gene assays illustrated that these bioactive lignans can activate hPXR. Additionally, they can all upregulate hPXR-regulate genes such as CYP3A4, UGT1A1 and OATP2 . Conclusion: These results clearly demonstrated the lignans from Schisandra sphenanthera exert hepatoprotective effects against LCA-induced cholestasis by activation of PXR. These lignans may provide an effective approach for the prevention and treatment of cholestatic liver injury. Graphical abstract: Image 1